Modulation of thermal properties of bovine collagen scaffold using variation of fabrication template - Amerai Khan, Nur Amnatasha; Shahbuddin, Munira; Busra, Mohd Fauzi (IIUM Press, 2023)
It has been a major challenge in the creation of synthetic or natural materials to favour the regeneration of the damaged tissues and organs. The fabrication methods and techniques of the scaffold directly influence with physical, chemical, and biological function of the cells when applied in in vivo and in vitro. Design of scaffolds for tissue regeneration requires an intimate knowledge of precise relationships between structure and biological function. These scaffolds can have a broad range of morphological properties, such as interconnecting (open pores), non-connecting (closed pores), or a combination of both. The physicochemical structure of collagen scaffold influences the repairing and tissue building to take place without contraction and scar formation. The goal of the current study is to study the relation of volume and area of exposure to freeze-drying process using different sizes of aluminium tray to achieve different thermophysical properties of collagen scaffolds. Freeze-drying of collagen scaffold is useful because the production of a glassy amorphous material with a Tg above room temperature (>32 oC) makes the scaffold stable and can be stored on the shelf. From this endeavor, we hypothesized that dimension of fabrication template and volume are able to influence thermal properties of collagen scaffold’s glass transition temperature (Tg).